Quality and Storage Stability Evaluation of Pangasius Fish (Pangasianodon hypophthalmus) Pickle Under Varied Temperature Conditions - Jakhar, J. K.; Sahu, Hinglaj; Chandravanshi, Roshani; Biswas, Karan; Sahu, Nihal; Sahu, Nilesh Kumar; Mugale, Rohini R.; Dhruve, Domendra (Fishery Technology, 2026)
A ready-to-eat fish pickle was developed from Pangasianodon hypophthalmus, and its storage stability was evaluated at room temperature (28–32 °C) and under refrigeration (5–8 °C) for six months. Quality changes were monitored through total volatile base nitrogen (TVB-N), peroxide value (PV), pH, total plate count (TPC), and sensory acceptability. TVB-N, PV, and TPC increased progressively under both conditions, with higher deterioration at room temperature. Sensory acceptability decreased from 8.8 to 3.1 at room temperature and to 6.4 under refrigeration. The product remained acceptable for four months at room temperature and six months under refrigerated storage.